THE ROLE AND EFFECTIVENESS OF DIGITAL TECHNOLOGIES IN MODERN EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the role of digital technologies in the modern education system, their impact on the learning process, and their effectiveness. It highlights the positive impact of innovative technologies such as distance learning platforms, artificial intelligence, virtual and augmented reality, and gamification on the quality and accessibility of education. Additionally, the problems arising in the process of digital transformation and ways to overcome them are examined.
Keywords: Digital technologies, distance learning, artificial intelligence, virtual reality, gamification, quality of education, innovative pedagogy, digital transformation